Investigating the Effectiveness of Customer Participation Behaviours: Evidence from Credence Goods - Cao, Ran (2013)
The trends of service-dominant logic and customer empowerment have make customer participation behaviours increasingly be interested by scholars and marketing practitioners. It has been noticed that a great number of literature on customer participation behaviour on an online context focus on the virtual communities, but a few have thoroughly investigated the increasing potential of company official websites. The effectiveness of various customer participation behaviours on this fast developing platform has not been sufficiently investigated. Furthermore, the increasing emergent of credence goods in the e-market has been neglected by customer participation behaviour literature. Therefore, this study was aimed to address these gaps and to investigate the effectiveness of customer participation behaviours on company official websites in credence goods context. A theoretical model was created based on the extant literature. Total 121 participants joined the research by conducting three online experiments and completing an Internet-based survey. The results from a series of quantitative analyses strongly supported the proposed model. The findings suggest that customer participation behaviours are able to effectively generate positive customer satisfaction and customer attitudinal loyalty, where customer trust is a key mediator.